2014
DOI: 10.1002/ajp.22323
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of tetanus toxoid inoculation on the demography and life expectancy of the Cayo Santiago rhesus macaques

Abstract: Tetanus was a major cause of mortality in the free-ranging population of rhesus monkeys on Cayo Santiago prior to 1985 when the entire colony was given its first dose of tetanus toxoid. The immediate reduction in mortality that followed tetanus toxoid inoculation (TTI) has been documented, but the long-term demographic effects of eliminating tetanus infections have not. This study uses the Cayo Santiago demographic database to construct comparative life tables 12 years before, and 12 years after, TTI. Life tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
1
16
0
1
Order By: Relevance
“…Changes in density are clearly identifiable because it is a closed island population. More importantly, this primate population exhibits a high annual population growth rate (λ > 1:10; Rawlins and Kessler 1986; Blomquist et al 2011; Kessler et al 2015) and exists frequently at relatively high densities where population dynamics are regulated by reduced reproduction (Hernández-Pacheco et al 2013, 2016a). …”
Section: Methodsmentioning
confidence: 99%
“…Changes in density are clearly identifiable because it is a closed island population. More importantly, this primate population exhibits a high annual population growth rate (λ > 1:10; Rawlins and Kessler 1986; Blomquist et al 2011; Kessler et al 2015) and exists frequently at relatively high densities where population dynamics are regulated by reduced reproduction (Hernández-Pacheco et al 2013, 2016a). …”
Section: Methodsmentioning
confidence: 99%
“…This was one of the first times that a disease was eradicated from any primate population, including human [Southwick, 1989]. Thirty years later, it was shown that the tetanus vaccination program caused significant long-term effects on the demographics of the population not only affecting mortality, but life expectancy and fecundity as well [Kessler et al, 2014]. …”
Section: Discussionmentioning
confidence: 99%
“…Animals are provisioned with 0.23/kg/animal/day of commercial monkey chow and water is available ad libitum. Veterinary intervention is minimal except during the annual trapping period when yearlings are captured, marked for identification, physical samples are collected (including blood samples for paternity testing), and tetanus inoculation is given [Kessler et al, 2014]. Severely injured animals are either removed from the island for treatment or euthanized in accordance with guidelines of the American Veterinary Medical Association.…”
Section: Methodsmentioning
confidence: 99%
“…It also establishes the importance of addressing density effects to optimize management strategies for the population. Given the expected reproductive value post-tetanus toxoid inoculation of the colony [Kessler et al, 2014] and density-dependence in fertility among adult females [Hernández-Pacheco et al, 2013], we hypothesize that the annual removal of adult females, and not immature individuals, will have the highest impact on the population growth and that the exponential growth following past removal events is the result of increased female fertility rates.…”
Section: Introductionmentioning
confidence: 99%